2012
DOI: 10.1002/app.37705
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and flammability studies of poly(vinyl alcohol) composites filled with sodium hydroxide

Abstract: Poly(vinyl alcohol) (PVA) is a polymer of great value due to its wide spread applications. The present article describes the effect of sodium hydroxide on the flammability, thermal degradation, and tensile strength properties of PVA. The PVA/sodium hydroxide composite films at different loading levels of sodium hydroxide, i.e., 0.5, 1, 2, 3, and 4.5 wt % were prepared by solution casting technique. Dynamic thermogravimetry was used to study the thermal degradation behavior of samples at four different linear h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…With the increase in char yield from 7.9 to as much as 23.5% (at 0.5% NaOH), approximately logarithmic relations between NaOH concentration and char yield are observed, with the data point at 0.001 being the only outlier; by increasing the addition levels of the base, the maximum mass-decomposition rates (dW/dT) dropped, as expected from 2.71 to under 2.0. Previously reported work by Arora and coworkers [28], examining the effects of as much as 5 wt% NaOH to PVA films, proposes that dehydration of alcohol groups in PVA likely commence at decreased temperatures when the alkaline agent is added-this is consistent with our proposed alkaline catalysis in PVA aerogels. The previous workers observed an increase in limiting oxygen index (LOI) from 20.5 to 27.2 with the incorporation of 4.5% NaOH.…”
Section: Thermal Stability and Degradation Mechanismsupporting
confidence: 90%
See 2 more Smart Citations
“…With the increase in char yield from 7.9 to as much as 23.5% (at 0.5% NaOH), approximately logarithmic relations between NaOH concentration and char yield are observed, with the data point at 0.001 being the only outlier; by increasing the addition levels of the base, the maximum mass-decomposition rates (dW/dT) dropped, as expected from 2.71 to under 2.0. Previously reported work by Arora and coworkers [28], examining the effects of as much as 5 wt% NaOH to PVA films, proposes that dehydration of alcohol groups in PVA likely commence at decreased temperatures when the alkaline agent is added-this is consistent with our proposed alkaline catalysis in PVA aerogels. The previous workers observed an increase in limiting oxygen index (LOI) from 20.5 to 27.2 with the incorporation of 4.5% NaOH.…”
Section: Thermal Stability and Degradation Mechanismsupporting
confidence: 90%
“…As can be seen in Table 2, the specific compressive moduli increased from 4.8 ± 1.6 to 16.3 ± 3.0 MPa cm 3 /g as the NaOH was increased from 0% to 9.1%. The increases in mechanical properties of the aerogels with increasing NaOH levels differs from the observed mechanical properties of PVA films, which incorporate that same additive [28]. Our previous work with PVA aerogels has shown that their mechanical properties are extremely sensitive to the skeletal density of aerogel "struts", which resemble the cellular walls in foams, as well as the morphology of the aerogels [3,5,[11][12][13].…”
Section: Apparent Density and Mechanical Performancementioning
confidence: 75%
See 1 more Smart Citation
“…[ 12 ] These previous reports mainly focused on mitigating the dissolution and structural distortion of the cathode materials by sophisticated material composition tuning and/or incorporation of flammable PVA electrolyte additives. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…These previous reports mainly focused on mitigating the dissolution and structural distortion of the cathode materials by sophisticated material composition tuning and/or incorporation of flammable PVA electrolyte additives. [13] The 30 m ZnCl 2 WISE was first introduced in 2018, [14] enabling a dendrite-free Zn metal anode with a high Coulombic efficiency (CE) of 95.4%. The same group applied the ZnCl 2 WISE to a Ca 0.20 V 2 O 5 •0.80H 2 O cathode, [1a] and demonstrated increased operating potential and specific capacity compared to those obtained in the 1 m counterpart.…”
Section: Introductionmentioning
confidence: 99%